ADOPTION OF DEVICE MANAGEMENT POLICIES AS TECHNIQUE FOR FRAUD PREVENTION BY MANAGEMENT STAFF IN TERTIARY INSTITUTIONS IN BAUCHI STATE (NAU Journal of Technology and Vocational Education, 2024)
This study ascertained adoption of device management policies as technique for fraud prevention in tertiary institutions in Bauchi State. One research question guided the study and one null hypothesis was tested. Descriptive survey research design was adopted for the study. The population comprised 696 management staff working in the six public tertiary institutions in Bauchi State. No sample was used because the population size was manageable for the researcher. A 13-items structured questionnaire was used. The instrument was validated by three experts. To determine the internal consistency of the items, Cronbach Alpha was used to determine the reliability co-efficient value of 0.79. Mean and standard deviation were used to answer the research questions, while Analysis of Variance was used to test the null hypotheses at 0.05 alpha levels. The findings of the study revealed that management staff disagrees on adoption device management policies as technique for fraud prevention in tertiary institutions in Bauchi State. Management staffs’ years of working experience do not significantly influence their mean ratings on the adoption of device management policies as technique for fraud prevention in tertiary institutions in Bauchi State. The study concluded that the device management policies as technique in the study are not adopted by management staff for fraud prevention in tertiary institutions in Bauchi State. It was recommended among others that business and office education lecturers should therefore ensure that data security management techniques such as device management policies are taught to their students when teaching about techniques for reducing fraud and are included in their business education curricula for the training of business education in tertiary institutions.
Keywords: Tertiary Institutions; Device Management Policies Techniques; Management Staff; Fraud Prevention